Surface hydrogen migration significantly promotes electroreduction of acetonitrile to ethylamine - Tang, Yulong; Li, Jiejie; Lin, Yichao; Cheng, Moxing; Wang, Shuibo; Tian, Ziqi; Zhou, Junjie; Zhang, Haolei; Wang, Yunan; Chen, Liang (Nature communications, 2025)
The electrochemical reduction of acetonitrile (AN) to ethylamine (EA) is an attractive yet challenging process, primarily due to the competing hydrogen evolution reaction (HER). This study demonstrates the ability to halt the HER at Volmer step, where protons migrate to the unsaturated bond of AN on a self-supported CuO@Cu heterostructure. The CuO@Cu catalyst exhibits nearly 100% Faradaic efficiency (FE) over the entire range of potentials tested from −0.1 to −0.4 V vs. RHE, demonstrating remarkable stability over 1000 h at a constant current density of 0.2 A cm −2 . CuO is identified as the active component driving the reaction, while the metallic Cu facilitates efficient electron transfer. Theoretical simulations and experimental evidences indicate that a synergistic hydrogenation process contributes to the AN reduction reaction (ARR), which involves both surface hydrogen migration and proton addition from solution. This study provides an insight into understanding of ARR process, and suggests an efficient strategy to enhance the electrochemical hydrogenation of organic molecules by regulating the Volmer step. The competing hydrogen evolution reaction (HER) presents a major challenge in achieving the selective acetonitrile reduction reaction (ARR) to ethylamine. Here, the authors report halting HER at the Volmer step on a CuO@Cu heterostructure, significantly promoting the selective ARR.